Comparison of tissue prolidase enzyme activity and serum oxidative stress level between pregnant women with placental abruption and those with a healthy pregnancy - (:unkn) unknown (SPRINGER HEIDELBERG, 2015)
Although placental abruption is an acute condition, it is thought that the underlying pathology is chronic vasculopathy. Collagen is one of the important components of vascular structure, and there is a correlation between collagen turnover and prolidase enzyme activity (PEA). Thus, our aim was to assess whether there is a difference in serum oxidative stress level and PEA between pregnant women with placental abruption and those with a healthy pregnancy. The study group consisted of 36 pregnant women who underwent caesarean section with a diagnosis of placental abruption, while the control group comprised 36 pregnant women who underwent caesarean section due to obstetric reasons. Venous blood samples were drawn from all patients before caesarean section. In addition, tissue samples were obtained during caesarean section to evaluate tissue PEA. No significant differences in demographic characteristics were detected between groups (p > 0.05). Oxidative stress parameters, such as total oxidant status and oxidative stress index, were found to be significantly higher in the study group (p < 0.001). Placental tissue PEA was found to be significantly higher in pregnant women with placental abruption (557.21 +/- A 135.41 vs. 426.68 +/- A 131.57 U/g, p < 0.001). In addition, a significant positive correlation was detected between PEA and oxidative stress parameters (r = 0.332, p = 0.004). Our results indicated that elevated tissue PEA and serum oxidative stress levels are closely related to placental abruption. Thus, we think that increased collagen turnover may have a significant role in the aetiopathogenesis of placental abruption.
Keywords: Placental abruption; Prolidase enzyme activity; Oxidative stress; Vasculopathy